2022
DOI: 10.3390/atmos13020239
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PM10 Levels Monitored in Bangkok and Its Vicinity Areas, Thailand

Abstract: The ambient air concentrations of PM10 were observed in Bangkok and its vicinity areas including Nonthaburi and Nakhon Pathom, Thailand. The selected study areas are located near heavy-traffic roads with a high concentration of traffic-related air pollution. The ambient air samples were collected in the winter season (October 2019 to February 2020). The highest average level of PM10 was found in Nonthaburi (66.63 µg/m3), followed by Bangkok (56.79 µg/m3) and Nakhon Pathom (40.18 µg/m3), respectively. The morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The metals with the highest concentrations in the sub-micron range were magnesium, aluminium, iron, zinc, copper and chromium. Phairuang et al ( 2021 ) also showed that iron, copper, magnesium, zinc, chromium, potassium, sodium and lead were high in the ultrafine (PM 0.1 ) range and Kanjanasiranont et al ( 2022 ) found that copper, chromium and iron were dominant in the ambient PM 10 concentration in Bangkok and its vicinity areas including Nonthaburi and Nakhon Pathom, Thailand.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metals with the highest concentrations in the sub-micron range were magnesium, aluminium, iron, zinc, copper and chromium. Phairuang et al ( 2021 ) also showed that iron, copper, magnesium, zinc, chromium, potassium, sodium and lead were high in the ultrafine (PM 0.1 ) range and Kanjanasiranont et al ( 2022 ) found that copper, chromium and iron were dominant in the ambient PM 10 concentration in Bangkok and its vicinity areas including Nonthaburi and Nakhon Pathom, Thailand.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Biomass burning peaks occur in Thailand and surrounding countries between December and March (Vadrevu et al 2019 ), and Dejchanchaiwong et al ( 2020 ) identified that high PM 2.5 and PM 0.1 concentration haze events in Bangkok during December 2018 were likely to be caused by aerosol transport from Cambodia and central and northeastern Thailand. Transmission electron microscopy (TEM) analysis of PM 1 particles measured between January and February 2020 in Bangkok revealed chains of spherical particles typical of combustion sources (Kanjanasiranont et al 2022 ). We measured some of the highest masses in February, March and April.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangkok, the capital city of Thailand, is one of the megacities in SEA with high concentrations of residents and traffic congestion. Many studies have concluded that the particulate pollution in the Bangkok metropolitan region (BMR) is mainly from land transportation [46][47][48][49]. The mass concentration of PM 0.1 in the BMR ranges from 7.7-18.9 µg/m 3, a number that is higher than that in Western countries such as those of Europe and the USA; however, it is in the same range as other Asian megacities such as Shanghai [50].…”
Section: Recent Studies Of Pmmentioning
confidence: 99%
“…In contrast, it contributes only slightly (10-20%) to the total PM concentration. [46,47,48,49]. The mass concentration of PM0.1 in the BMR ranges from 7.7 -18.9 (µg/m 3 ) a number that is higher than that in western countries such as Europe and the USA; however, it is in the same range as other Asian megacities such as Shanghai [50].…”
Section: Pm01 Particle Mass Concentration and Particle Number Concent...mentioning
confidence: 93%